Analisis Kinerja Simpang Empat Tak Bersinyal (Studi Kasus: Jalan Ikan Tombro – Jalan Sudimoro, Kecamatan Lowokwaru, Kota Malang) - Iman Joetam Brian Malo; Andy Kristafi Arifianto; M. Sa’dillah (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
The problem of traffic congestion has not yet been fully resolved in Indonesian cities such as Malang. One of the areas most prone to traffic jams is the intersection of Sudimoro Street and Lowokwaru District. Due to the lack of traffic signs at that location, vehicles drive erratically, disrupting traffic flow. Because it is located in an area frequented by young people—such as cafes and trendy hangout spots—the intersection of Sudimoro Street and Ikan Tombro Street, particularly north of the airplane roundabout, experiences fairly heavy traffic. This research approach, which examines the current performance of the interchange and its projected performance in 2030, is based on the Indonesian Road Capacity Guidelines (PKJI 2023). The interchange currently has a capacity of 2,664.56 vehicles per hour, a saturation level of 0.70, an average delay of 11.89 seconds per vehicle, and a queueing probability ranging from -0.21% to 40.67%, according to the study’s findings. The interchange’s service level is classified as Class F. According to projections, traffic volume will reach 3,550.24 vehicles per hour by 2030, the saturation level will rise to 1.33, and the service quality will remain in Class F.